Assessment of renal allograft fibrosis by transient elastography. (6th February 2013) - Sommerer, Claudia; Scharf, Michael; Seitz, Christoph; Millonig, Gunda; Seitz, Helmut K.; Zeier, Martin; Mueller, Sebastian
Summary Transient elastography (TE, Fibroscan) has been established as a noninvasive assessment tool of liver fibrosis. We evaluated potentials and limitations of TE for identifying renal allograft fibrosis. The technical possibility of kidney examination by TE was assessed in two 10‐week‐old German landrace pigs and kidney stiffness (KS) was evaluated in 164 renal transplant patients. KS could be determined in all animals at the pole and pars media (29 ± 10 kPa vs. 31 ± 17 kPa). In human renal allografts KS was successfully performed in 94.5% of the test series with reliable results in 72% of the measurements. Mean KS at the pole or pars media were comparable (35.0 ± 19.9 kPa vs. 33.2 ± 18.6 kPa). Significantly higher KS was detected in renal allografts with histologically confirmed advanced fibrosis. Body‐mass‐index, skin‐allograft distance, and peri or intrarenal fluid accumulation were important confounders of successful KS measurements (BMI: r = −0.31; P < 0.001; distance: r = −0.50; P < 0.001). Notably, KS did not correlate with renal function. TE represents a noninvasive approach in selected transplant recipients to identify allografts with severe fibrosis. The heterogeneous kidney morphology and several other confounding factors negatively affect measurability of KS by TE. Further technical modifications are required to improve applicability of TE for kidney assessment.